Pandemic‐Related Stress, Coping, and Wellbeing in an International and Multi‐Ethnic Cohort of Older Adults. (20th December 2022) - Medina, Luis D; Franco, Idalid; Thumala, Daniela; Miranda‐Castillo, Claudia; Acosta, Daisy M; Aguero, Cinthya; Aguilar‐Navarro, Sara Gloria; Baena, Ana Y.; Brucki, Sonia; Bustin, Julian; Duque, Lissette; Velazquez, Ivonne Z. Jimenez; et al.
Abstract: Background: The COVID‐19 pandemic has impacted the wellbeing of older adults. Pandemic‐related stress has implications on cognitive status, including decline due to Alzheimer's disease and related dementias. Yet, evidence suggests that COVID‐19 has impacted culturally and linguistically diverse communities differently. We sought to examine the role of COVID‐19 on coping and wellbeing in an international, multi‐ethnic sample of older adults. Method: Data from 955 older adults (age = 66.7±7.9 years; education = 15.2±5.9 years; 71% female; 41% Hispanic/Latino) were pulled from a larger, international sample examining the response of older adults to COVID‐19. All participants completed demographic questionnaires, measures of psychological distress, the Brief‐COPE – a 28‐item self‐report questionnaire used to measure respondent's efforts to minimize distress from a stressful life event – and the Epidemic‐Pandemic Impacts Inventory (EPII) – a 92‐item inventory of pandemic related experiences across several life domains. Using linear regression, we examined relationships between Brief‐COPE scores, ethnicity, and select EPII items controlling for several covariates (age, sex, education, marital status, number of children, employment status, household income, and history of COVID‐19 symptoms) in all analyses. Result: Hispanic/Latino (H/L) ethnicity was associated with slightly higher scores on the approach‐focused coping subscale compared to the non‐Hispanic White (NHW) group (Approach: 27.3±6.6 vs 26.1±6.1; B = 1.205, p = 0.015, CI: 0.238, 2.172). There was no effect of ethnicity on Brief‐COPE Total or Avoidance subscale scores (both p s>0.050). Notably, review of covariates suggested increased age was associated with lower scores on Approach (B = ‐0.065, p = 0.041, CI: ‐0.128, ‐0.003), Avoidance (B = ‐0.054, p = 0.034, CI: ‐0.104, ‐0.004), and Total scores (B = ‐0.136, p = 0.028, CI: ‐0.257, ‐0.015). Higher Approach scores were associated with greater endorsement of Positive Life Changes in both ethnic groups (NHW: partial r = 0.298, p <0.001; H/L: partial r = 0.249, p <0.036), but with endorsement of Mental Health Problems in NHWs only (NHW: partial r = 0.144; p = 0.001; H/L: partial r = ‐0.019, p >0.050). Conclusion: Findings suggest cross‐cultural differences in the stress coping response of older adults during the pandemic, even after controlling for symptomatic history and other relevant covariates. Moreover, coping may be differentially related to positive and negative outcomes across cultural groups. These results support the need to consider cultural background when considering coping and wellbeing in older adults.